Complete mitochondrial genomes of three troglophile cave spiders (Mesabolivar, pholcidae) - Renato Renison Moreira Oliveira; Santelmo Vasconcelos; Eder Soares Pires; Thadeu Pietrobon; Xavier Prous; Guilherme Oliveira (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we report the first complete mitochondrial genome of three Mesabolivar specimens found in the interior of N4E_0023 cave from Serra Norte (Carajás), Parauapebas (Brazil). The three mitogenomes contain 14,941, 14,845 and 14,727 bp, and GC content of 29.41%, 31.68% and 29.34%, respectively. All three mitogenomes include 13 protein-coding genes, 17 transfer RNA (tRNA) genes, five putative transfer RNA (tRNA) genes and two ribosomal RNA (16S and 12S rRNA). We also performed a phylogenetic analysis with the concatenated coding genes from the complete mitochondrial genomes and showed that the analyzed Mesabolibar specimens clustered together in a clade, sister to the group with two Pholcus species, the other Pholcidae species with available mitogenome.